(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2025)
A field experiment was conducted in an experimental field affiliated with the College of Agricultural Engineering Sciences, University of Baghdad, Al-Jadriya, during the fall season of 2022. Split plot arrangement in the Randomized Complete Block Design (RCBD) of three replicates was used comprising three levels of sulfur (0, 500, and 1000 kg ha-1) symbolized by S0, S1, and S2 forming the main plots, added to the soil before planting before two months, while the subplots were the bio-fertilizers represented by B0 and B1. Results showed the superiority of the second level of agricultural sulfur, giving the highest traits involving the plant height reaching 79.2 cm, chlorophyll content that was 91.1 SPAD, total yield was 44.0 mg ha-1 and protein content was 18.38%. The biofertilization was also superior in giving the highest traits involving the plant height was 80.2 cm, chlorophyll content was 98.9 SPAD and flower disc diameter was 23. 53 cm, total yield was 43.6 mg ha-1 and protein content was 18.94%, the concentration of the active substance sulforaphane in flower disc was 38.1 mg kg-1 fresh weight. For the binary interaction, the treatment of biofertilization with the third level of agricultural sulfur was superior, giving the highest values for the qualities in the plant height was 81.5 cm and the flower disc diameter was 23. 92 cm and the total yield was 45.7 mg ha-1, the percentage of protein in the amount of 19.31% and the concentration of the active substance sulforaphane in flower disk was 47.8 mg kg-1 fresh weight.